P(X=k)= p(1-p)^k-1 k=1,2,3.... 0 elesewhere Show that Mx(t)= pe^t 1-(1-p)e^t for t=( -infinity, ln 1/1-p) I know mgf is intergration of e^fx*fx(x) dx please help thanx in advance
Follow Math Help Forum on Facebook and Google+
Originally Posted by Hyungmin P(X=k)= p(1-p)^k-1 k=1,2,3.... 0 elesewhere Show that Mx(t)= pe^t 1-(1-p)e^t for t=( -infinity, ln 1/1-p) I know mgf is intergration of e^fx*fx(x) dx please help thanx in advance Read this: http://www.mathhelpforum.com/math-he...97251-mgf.html Thread closed.
View Tag Cloud